Psycho-Social Measures for Cultivating Positive Mental Health in Individuals for Sustainable Communities in Anambra State (West African Journal on Sustainable Development, 2024)
Good mental health promotes interpersonal relationship, civic engagements and responsibility as well as socio-economic development and therefore is paramount to achieving the Sustainable Development Goals (SDGs) in any nation, state or community. Unfortunately, the mental health of some residents in Anambra state has been attacked in recent times as a result of unprecedented challenges ranging from insecurity, heightened inflation, overwhelming poverty, hunger, untold hardship and unemployment among others. The challenges which seem enormous exert pressure, stress, anxiety and depression on some individuals. It also triggers extreme behavioural acts such as suicidal ideation and suicide on the below average individuals’ thus erupting poor mental health. Poor mental health breeds dysfunctional and chaotic communities. Poor mental health hinders adaptation, adjustment and collaboration which are crucial for societal growth and development. This paper however tries to suggest psycho-social measures for cultivating positive mental health in individuals for sustainable communities in Anambra state. Among other such psycho-social measures include building of emotional resilience, encouraging positive actions such as self expression, developing coping skills and developing a sense of meaning and purpose in life.
Keywords: Psycho-social; good mental health and sustainable communities